Upaya Meningkatkan Hasil Belajar Lari Sprint Melalui Permainan Smart Speed Flag Pada Siswa Kelas Iv Sd Negeri Klepu 04 Kecamatan Pringapus Kabupaten Semarang Tahun Pelajaran 2020/2021 (Indonesian Journal for Physical Education and Sport, 2021)
This study aims to determine the Improvement of Sprint Running Learning Outcomes Using the Smart Speed ​​Flag Game in Grade IV Students of SD Negeri Klepu 04, Pringapus District, Semarang Regency for the 2020/2021 Academic Year. The subjects in this study were fourth grade students with a total of 26 students. The method used in this research is Classroom Action Research. The results showed that in the first cycle there were 12 students (46.15%) who achieved mastery while 14 students (53.85%) had not achieved learning mastery, this indicates that the target that the researcher wants is 60% of the number of students has not been achieved so that must be improved again. Cycle II as many as 24 students (92.30%) who have achieved complete learning and 2 students who are still not complete (7.7%). The conclusion of the research is that through the smart speed flag game, it can have an influence in an effort to improve learning outcomes for sprinting in fourth grade students of SD Negeri Klepu 04, Pringapus District, Semarang Regency, for the 2020/2021 Academic Year.